1998
DOI: 10.1902/annals.1998.3.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Disease and Diabetes Mellitus: A Two‐Way Relationship

Abstract: Severe periodontal disease often coexists with severe diabetes mellitus. Diabetes is a risk factor for severe periodontal disease. A model is presented whereby severe periodontal disease increases the severity of diabetes mellitus and complicates metabolic control. We propose that an infection-mediated upregulation cycle of cytokine synthesis and secretion by chronic stimulus from lipopolysaccharide (LPS) and products of periodontopathic organisms may amplify the magnitude of the advanced glycation end product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
556
1
35

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 688 publications
(608 citation statements)
references
References 52 publications
16
556
1
35
Order By: Relevance
“…This result is in agreement with various other studies [5,7,41]. In periodontitis, the elevated NO is due to the increased expression of iNOS by the PMNs, macrophages, and endothelial cells.…”
Section: Discussionsupporting
confidence: 93%
“…This result is in agreement with various other studies [5,7,41]. In periodontitis, the elevated NO is due to the increased expression of iNOS by the PMNs, macrophages, and endothelial cells.…”
Section: Discussionsupporting
confidence: 93%
“…It has been shown that periodontal infections can change the metabolic-endocrine status of the host, leading to difficulties in the control of blood sugar levels, which can contribute to insulin-resistance, hyperglycemia and complications in the metabolic control of diabetes mellitus 2,11,15 . Moreover, periodontal treatment improves diabetes control 2 .…”
Section: Discussionmentioning
confidence: 99%
“…15 The existence of vascular changes in the form of capillary basal membrane thickening due hyperglicemic conditions, also causes disruption of the nutrients and the migration of immune cells into the periodontal tissue. 12 Calprotectin (MRP8 /MRP14) is cytosolic protein that has important functions as chemotactic factor associated with the activation of monocytes and neutrophils, and accumulation of cells of innate immunity in areas of inflammation as well as an antibacterial protein.…”
Section: Discussionmentioning
confidence: 99%